Analysis dangerous of natural disaster. Disasters definitio and types. Aware of natural disaster - Khalilova Khurshida Teshaevna; Uralova Gulbakhor Uktamovna; Ravshanova Umida Bakhriddinovna (The Bioscan, 2025)
The Tashkent earthquake of 1966 stands as a pivotal moment in Central Asian history, reshaping not only the physical landscape of Uzbekistan's capital but also its socio-economic trajectory. This comprehensive study examines the multifaceted impacts of this seismic event, exploring both its immediate devastation and the long-term implications for urban development and disaster preparedness. Through an extensive review of contemporary accounts, scientific literature, and archival data, we analyze the geological factors that contributed to the earthquake's intensity, the effectiveness of the immediate response efforts, and the subsequent reconstruction initiatives. Our research highlights the unique challenges faced by a Soviet-era city in recovery, including the interplay between centralized planning and local needs. We evaluate the innovative architectural and engineering solutions employed in rebuilding Tashkent, which not only addressed seismic resilience but also modernized the urban fabric. Furthermore, this study assesses the evolving understanding of seismic risk in the region and how it has informed policy decisions and building practices over the subsequent decades. By examining the Tashkent earthquake through the lens of sustainable development, we identify key lessons applicable to modern urban resilience strategies. Our findings underscore the importance of integrating traditional knowledge with cutting-edge seismological research, the need for flexible and adaptive urban planning, and the critical role of community engagement in disaster recovery. This article contributes to the broader discourse on urban resilience, offering insights that can inform preparedness and response strategies for future seismic events in rapidly developing urban centers worldwide.